Tests of circular concrete-filled steel tubular stub columns with artificial notches representing local corrosions. (1st September 2021) - Huang, Haijia; Guo, Lanhui; Qu, Bing; Jia, Chen; Elchalakani, Mohamed
Highlights: Thirty circular concrete-filled steel tubular stub columns were tested. The computer model was developed and validated by the test results. The failure modes of notched specimens were different from that of intact specimens. The peak resistance and ductility decrease with the increasing of vertical and slope notch length. A practical model to compute the peak resistance of notched circular CFST was proposed. Abstract: Concrete-filled steel tubular (CFST) columns have been used in civil structures due to their affordability, high strength, superior ductility, and demonstrated fire resistance. However, there are remaining issues regarding the performances of the CFST columns with the locally corroded steel tubes, hindering the widespread acceptance of this type of members in practice. This paper focused on the circular CFST stub columns in which the steel tubes are locally corroded. To develop the critical data needed for understanding the behavior of such stub columns, a group of thirty specimens were designed, constructed and tested. Based on the recommendations from prior research, the local corrosions in the steel tubes of the specimens were represented by the artificial notches. The test parameters varied among the specimens included the notch orientations, lengths, depths, and widths. The test results revealed the influences of these parameters on different aspects of the responses of the stub columns with the corroded steel tubes. Computer models were also developed for the specimens and validated by the test results. Based on the test results and the results from parametric analyses using the validated computer models, a practical model to compute the peak resistance of a CFST stub column with the locally corroded steel tube was proposed and verified.